The Evolution of Earned, Transparent, and Quantifiable Faculty Salary Compensation - Kathleen H. Burns MD, PhD; Michael J. Borowitz MD, PhD; Karen C. Carroll MD; Christopher D. Gocke MD; Jody E. Hooper MD; Timothy Amukele MD, PhD; Aaron A. R. Tobian MD, PhD; Allen Valentine MBA, C (ASCP); Rob Kahl AA; Vanessa Rodas-Eral MS; John K. Boitnott MD; J. Brooks Jackson MD, MBA; et al. (Elsevier, 2018)
Faculty value equitable and transparent policies for determining salaries and expect their compensation to compare favorably to the marketplace. Academic institutions use compensation to recruit and retain talented faculty as well as to reward accomplishment. Institutions are therefore working to decrease salary disparities that appear arbitrary or reflect long-standing biases and to identify metrics for merit-based remuneration. Ours is a large academic pathology department with 97 tenure-track faculty. Faculty salaries are comprised of 3 parts (A + B + C). Part A is determined by the type of appointment and years at rank; part B recognizes defined administrative, educational, or clinical roles; and part C is a bonus to reward and incentivize activities that forward the missions of the department and medical school. A policy for part C allocations was first codified and approved by department faculty in 1993. It rewarded performance using a semiquantitative scale, based on subjective evaluations of the department director (chair) in consultation with deputy directors (vice chairs) and division directors. Faculty could not directly calculate their part C, and distributions data were not widely disclosed. Over the last 2 years (2015-2017), we have implemented a more objective formula for quantifying an earned part C, which is primarily designed to recognize scholarship in the form of research productivity, educational excellence, and clinical quality improvement. Here, we share our experience with this approach, reviewing part C calculations as made for individual faculty members, providing a global view of the resulting allocations, and considering how the process and outcomes reflect our values.